The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/aud.0b013e318031547a
|View full text |Cite
|
Sign up to set email alerts
|

Music Recognition, Music Listening, and Word Recognition by Deaf Children with Cochlear Implants

Abstract: Child implant users enjoy music more than adult implant users. Moreover, younger age at implantation increases children's engagement with music, which may enhance their progress in other auditory domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 23 publications
4
50
2
3
Order By: Relevance
“…This finding is also consistent with the reports which support that the auditory training not only improves the performance in the targeted listening task, but also the improvement often generalized the auditory tasks that were not explicitly trained [20]. The association between musical training and word recognition is also explained by the effect of focused music listening on training of auditory attention [21]. In other words, learning that occurs in the parameters of music may transfer to other auditory contexts such as verbal memory [36], and sensitivity to prosody [37].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is also consistent with the reports which support that the auditory training not only improves the performance in the targeted listening task, but also the improvement often generalized the auditory tasks that were not explicitly trained [20]. The association between musical training and word recognition is also explained by the effect of focused music listening on training of auditory attention [21]. In other words, learning that occurs in the parameters of music may transfer to other auditory contexts such as verbal memory [36], and sensitivity to prosody [37].…”
Section: Discussionsupporting
confidence: 93%
“…As Mitani et al [21] have reported that children with cochlear implants enjoy music more than adult implant users. Moreover, younger age at implantation increases children's engagement with music, which may enhance their progress in other auditory domains.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the present findings indicate that young CI users can discern the emotional intentions expressed in music, they shed no light on the emotional consequences of music for CI users. There are indications that young CI users enjoy music (Mitani et al, 2007;Stordahl, 2002;Vongpaisal et al, 2006), but it remains to be determined whether they experience changes in arousal and mood comparable to those experienced by individuals with NH (e.g. Balkwill and Thompson, 1999;Husain et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…For example, a song could sound natural to an EDLI but mechanical to a NH person listening to CI simulations because of the different states of the auditory exposure and memories of individuals. As a result, different listener groups may be making their music judgment using different standards and reference points (9,23,33). Moreover, the additional benefit of the implant for music perception compared with the music perception during the period of deafness using a hearing aid may also differ.…”
Section: Self-perceived Enjoyment and Perception Of Musicmentioning
confidence: 95%